Identity of England - Colls, Robert (Oxford University Press, 2004)
The English stand now in need of a new sense of home and belonging - a reassessment of who they are. This is a history of who they were, written from the perspective of the twenty-first century. It begins by considering how the English state identified an English nation which, from very early days, seems to have seen itself as not simply the creature of state or king. It considers also how in modern times the English nation survived shattering revolutions in technology, urban living, andglobal conflict, while at the same time retaining a softer, more human vision of themselves as a people in touch with their nature and their land. They claimed that there was more to living in England than work and wages, there was more to running a vast empire than just exploiting it. For all its faults and inequalities, they identified with their state. For all their shortcomings they were confident of their place in history. As little as forty years ago, these ideas were not much in doubt. Though vague and often contradictory, they held together as the English people held together -as a whole. Indeed, 'Englishness' was hardly recognized as a subject for analysis, except perhaps in a rather ironic and self-mocking vein. But now 'the national question' is back and history is at the top of the agenda. From a rich store of historical memory and possibility, Robert Colls connects the identity of England in the past with the changing and uncertain identity of England today.